Darcy-Brinkman free convection about a wedge and a cone subjected to a mixed thermal boundary condition - G. Ramanaiah; V. Kumaran (International Journal of Mathematics and Mathematical Sciences)
The Darcy-Brinkman free convection near a wedge and a cone in a porous medium with high porosity has been considered. The surfaces are subjected to a mixed thermal boundary condition characterized by a parameter m; m=0, 1, ∞ correspond to the cases of prescribed temperature, prescribed heat flux and prescribed heat transfer coefficient respectively. It is shown that the solutions for different m are dependent and a transformation group has been found, through which one can get solution for any m provided solution for a particular value of m is known. The effects of Darcy number on skin friction and rate of heat transfer are analyzed.